Pluripotent stem cell-derived bile canaliculi-forming hepatocytes to study genetic liver diseases involving hepatocyte polarity - Overeem, Arend W.; Klappe, Karin; Parisi, Silvia; Klöters-Plachky, Petra; Mataković, Lavinija; du Teil Espina, Marines; Drouin, Christian A.; Weiss, Karl Heinz; van IJzendoorn, Sven C. D. (Journal of hepatology, 2019)
Background & Aims - Hepatocyte polarity is essential for the development of bile canaliculi and for safely transporting bile and waste products from the liver. Functional studies of autologous mutated proteins in the context of the polarized hepatocyte have been challenging because of the lack of appropriate cell models. The aims of this study were to obtain a patient-specific hepatocyte model that recapitulated hepatocyte polarity and to employ this model to study endogenous mutant proteins in liver diseases that involve hepatocyte polarity. - Methods - Urine cell-derived pluripotent stem cells, taken from a patient with a homozygous mutation in ATP7B and a patient with a heterozygous mutation, were differentiated towards hepatocyte-like cells (hiHeps). HiHeps were also derived from a patient with MEDNIK syndrome. - Results - Polarized hiHeps that formed in vivo-like bile canaliculi could be generated from embryonic and patient urine cell-derived pluripotent stem cells. HiHeps recapitulated polarized protein trafficking processes, exemplified by the Cu2+-induced redistribution of the copper transporter protein ATP7B to the bile canalicular domain. We demonstrated that, in contrast to the current dogma, the most frequent yet enigmatic Wilson disease-causing ATP7B-H1069Q mutation per se did not preclude trafficking of ATP7B to the trans-Golgi Network. Instead, it prevented its Cu2+-induced polarized redistribution to the bile canalicular domain, which could not be reversed by pharmacological folding chaperones. Finally, we demonstrate that hiHeps from a patient with MEDNIK syndrome, suffering from liver copper overload of unclear etiology, showed no defect in the Cu2+-induced redistribution of ATP7B to the bile canaliculi. - Conclusions - Functional cell polarity can be achieved in patient pluripotent stem cell-derived hiHeps, enabling, for the first time, the study of the endogenous mutant proteins, patient-specific pathogenesis and drug responses for diseases where hepatocyte polarity is a key factor. - Lay summary - This study demonstrates that cells that are isolated from urine can be reprogrammed in a dish towards hepatocytes that display architectural characteristics similar to those seen in the intact liver. The application of this methodology to cells from patients diagnosed with inherited copper metabolism-related liver diseases (that is, Wilson disease and MEDNIK syndrome) revealed unexpected and novel insights into patient mutation-specific disease mechanisms and drug responses.